2017
DOI: 10.18632/oncotarget.14944
|View full text |Cite
|
Sign up to set email alerts
|

Novel HBsAg mutations correlate with hepatocellular carcinoma, hamper HBsAg secretion and promote cell proliferation in vitro

Abstract: BackgroundAn impaired HBsAg-secretion can increase HBV oncogenic-properties. Here, we investigate genetic-determinants in HBsAg correlated with HBV-induced hepatocellular carcinoma (HCC), and their impact on HBsAg-secretion and cell-proliferation.MethodsThis study included 128 chronically HBV-infected patients: 23 with HCC (73.9% D; 26.1% A HBV-genotype), and 105 without cirrhosis/HCC (72.4% D, 27.6% A) as reference-group. The impact of mutations on HBsAg-secretion was assessed by measuring the ratio [secreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 38 publications
(48 reference statements)
0
15
1
Order By: Relevance
“…Mutations in this domain can result in a stable, glycosylated, but nonsecreted chain, thus affecting the biogenesis and secretion of subviral particles[ 77 ]. Two C-terminus S mutations were found and significantly correlated with HCC: P203Q (4/23, 17.4% in HCC vs 1/105, 1.0 in non-HCC, P = 0.004); S210R (8/23, 34.8% in HCC vs 4/105, 3.8% in non-HCC, P < 0.001); P203Q + S210R (4/23, 17.4% in HCC vs 0/110, 0 in non-HCC, P = 0.001)[ 78 ]. In vitro experiments revealed that P203Q, S210R, and P203Q+S210R significantly reduced the ratio of secreted and intracellular HBsAg compared with WT at each time point analyzed ( P < 0.05); P203Q and P203Q+S210R increased the percentage of cells in S-phase compared with WT (P203Q: 26% ± 13%; P203Q+S210R: 29% ± 14%; WT: 18% ± 9%, P < 0.01); S210R increased the percentage of cells in the G2/M-phase (33% ± 6% for S210R vs 26% ± 8% for WT, P < 0.001)[ 78 ].…”
Section: Association Between Hbv Pre-s/s Variants and Liver Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in this domain can result in a stable, glycosylated, but nonsecreted chain, thus affecting the biogenesis and secretion of subviral particles[ 77 ]. Two C-terminus S mutations were found and significantly correlated with HCC: P203Q (4/23, 17.4% in HCC vs 1/105, 1.0 in non-HCC, P = 0.004); S210R (8/23, 34.8% in HCC vs 4/105, 3.8% in non-HCC, P < 0.001); P203Q + S210R (4/23, 17.4% in HCC vs 0/110, 0 in non-HCC, P = 0.001)[ 78 ]. In vitro experiments revealed that P203Q, S210R, and P203Q+S210R significantly reduced the ratio of secreted and intracellular HBsAg compared with WT at each time point analyzed ( P < 0.05); P203Q and P203Q+S210R increased the percentage of cells in S-phase compared with WT (P203Q: 26% ± 13%; P203Q+S210R: 29% ± 14%; WT: 18% ± 9%, P < 0.01); S210R increased the percentage of cells in the G2/M-phase (33% ± 6% for S210R vs 26% ± 8% for WT, P < 0.001)[ 78 ].…”
Section: Association Between Hbv Pre-s/s Variants and Liver Diseasesmentioning
confidence: 99%
“…Two C-terminus S mutations were found and significantly correlated with HCC: P203Q (4/23, 17.4% in HCC vs 1/105, 1.0 in non-HCC, P = 0.004); S210R (8/23, 34.8% in HCC vs 4/105, 3.8% in non-HCC, P < 0.001); P203Q + S210R (4/23, 17.4% in HCC vs 0/110, 0 in non-HCC, P = 0.001)[ 78 ]. In vitro experiments revealed that P203Q, S210R, and P203Q+S210R significantly reduced the ratio of secreted and intracellular HBsAg compared with WT at each time point analyzed ( P < 0.05); P203Q and P203Q+S210R increased the percentage of cells in S-phase compared with WT (P203Q: 26% ± 13%; P203Q+S210R: 29% ± 14%; WT: 18% ± 9%, P < 0.01); S210R increased the percentage of cells in the G2/M-phase (33% ± 6% for S210R vs 26% ± 8% for WT, P < 0.001)[ 78 ]. These results show that these two C-terminus S mutations, P203Q and S210R, hamper HBsAg secretion and are associated with increased cellular proliferation, supporting their involvement in HCC development.…”
Section: Association Between Hbv Pre-s/s Variants and Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This occurs in NA monotherapy . It has been demonstrated that this large protein is oncogenic . In this study, 37% of the patients were transplanted for HCC.…”
Section: Discussionmentioning
confidence: 80%
“…Genomic mutations were significantly involved in the development of HBV-related HCC. P203Q and S210R which are mutations in HBsAg C-terminus hamper HBsAg-secretion and correlate with increased cellular proliferation and HBV-induced HCC [ 5 ]. A meta-analysis performed by Tian T et al indicated that miR-146a C>G increased HBV-related HCC risk while miR-196a-2 C>T decreased the risk of HBV-related HCC, especially in the Chinese population [ 6 ].…”
Section: Introductionmentioning
confidence: 99%